Birds of Katerniaghat Wildlife Sanctuary, Uttar Pradesh, India - Sethy, Janmejay; Chauhan, N. P. S. (Indian Forester, 2011)
A survey on birds was carried out from March 2007 to August 2007. The birds were observed during most active period of the day i.e. 0515 to 0830 hrs and 1530 to 1830 hrs. A total of 200 bird species were recorded in the sanctuary. The frequency of sightings of 62 bird species was very high. Out of total, 105 species were seen quite regularly and 35 birds were seen intermittently. Previous study of birds conducted during 2003 showed presence of 157 species in this sanctuary. The majority of species were recorded in mixed forest (n=145), followed by teak plantation (n=38) and rest from road side and open forest. Ninety one bird species (45.5%) species were resident breeding birds, including the Bengal florican and Swamp francolin. Another 31 (15.5%) were resident, but their breeding in Katerniaghat has not been confirmed. Winter migrants constituted at least 50 (25%) of the total species. The majority of these were waterfowl and also several species of leaf warblers (Phylloscopus spp.). Five (2.5%) species were summer migrants, showed local movement. Three species (1.5%), namely, the black redstart (Phoenicurus ochruros), blue rock thrush (Monticola solitaries) and blue whistling thrush (Myophonus caeruleus) were transient in this area. The status of about 20 species (10%) could not be ascertained.